Ski Negatively Regulates Erythroid Differentiation through Its Interaction with GATA1 - Ueki, Nobuhide (American Society for Microbiology, 2004)
The Ski oncoprotein dramatically affects cell growth, differentiation, and/or survival. Recently, Ski was shown to act in distinct signaling pathways including those involving nuclear receptors, transforming growth factor β, and tumor suppressors. These divergent roles of Ski are probably dependent on Ski's capacity to bind multiple partners with disparate functions. In particular, Ski alters the growth and differentiation program of erythroid progenitor cells, leading to malignant leukemia. However, the mechanism underlying this important effect has remained elusive. Here we show that Ski interacts with GATA1, a transcription factor essential in erythropoiesis. Using a Ski mutant deficient in GATA1 binding, we show that this Ski-GATA1 interaction is critical for Ski's ability to repress GATA1-mediated transcription and block erythroid differentiation. Furthermore, the repression of GATA1-mediated transcription involves Ski's ability to block DNA binding of GATA1. This finding is in marked contrast to those in previous reports on the mechanism of repression by Ski, which have described a model involving the recruitment of corepressors into DNA-bound transcription complexes. We propose that Ski cooperates in the process of transformation in erythroid cells by interfering with GATA1 function, thereby contributing to erythroleukemia.